PROPOSED GROWTH STRATEGY OF NEW INVESTMENT MANAGEMENT COMPANY (CASE STUDY: FAM INVESTMENT) - Dhiaputra, Ilham
The capital market industry is a fast-growing industry, especially in Indonesia. In the past five years, the number of individual investors in Indonesia grew by more than 400%. Until the end of 2019, the number of investors in Indonesia has reached 2.47 million. The investment manager is one of the business sectors that benefit from the continued development of the capital market industry. FAM Investment as one of the new companies in the field of investment managers trying to develop business performance both from the number of investors and the number of funds managed. The purpose of this research is to find out what strategies can make FAM Investment develop its business. This research conducted by a qualitative method. The data obtained from in-depth interviews with customers, prospective customers, and stockholders of the investment management business. It also conducted benchmarking on investment management companies both in Indonesia and in the world. The limitation of this study is that FAM Investment is a case, a company that has only been fully operational in two years. Analysis of the data obtained using internal and external analysis. For internal analysis, several analyzes, such as Resource-Based View, VRIO, and Core Competency, are used to determine the company's internal condition. External analysis carried out with industry analysis, competitor analysis, and PESTEL analysis, which focuses on the legal department. After analyzing, it was found that the main problem that hampered FAM Investment business growth was the legal problem. This legal problem occurs because there is no legal certainty for FAM Investment or its customers so that FAM Investment has the potential to be sued legally, both by its customers and by the regulator, namely the OJK. Then the researcher uses the TOWS analysis to determine the possibilities of a solution for FAM Investment, which is then chosen by a cost-benefit analysis. From the analysis, it found that the right solution to the current condition of FAM Investment is to change the form of the company into an investment company and add new products in the form of investment advisors to be able to serve more extensive customers. This research proves that the key to the success of investment companies is not just a matter of capital, but there are other aspects such as legal certainty, trust, and proper risk management